CDX2 autoregulation in human intestinal metaplasia of the stomach: impact on the stability of the phenotype. Issue 3 (9th December 2010) - Barros, Rita; da Costa, Luis Teixeira; Pinto-de-Sousa, João; Duluc, Isabelle; Freund, Jean-Noel; David, Leonor; Almeida, Raquel
Abstract : Background and aims: Intestinal metaplasia (IM) is a gastric preneoplastic lesion that appears following Helicobacter pylori infection and confers an increased risk for development of cancer. It is induced by gastric expression of the intestine-specific transcription factor CDX2. The regulatory mechanisms involved in triggering and maintaining gastric CDX2 expression have not been fully elucidated. The Cdx2 +/− mouse develops intestinal polyps with gastric differentiation and total loss of Cdx2 expression in the absence of structural loss of the second allele, suggesting a regulatory defect. This putative haplo-insufficiency, together with the apparent stability of IM, led to the hypothesis that CDX2 regulates its own expression through an autoregulatory loop in both contexts. Methods: Gastrointestinal cell lines were co-transfected with wild-type or mutated Cdx2 promoter constructs and CDX2 expression vector for luciferase assays. Transfection experiments were also used to assess endogenous CDX2 autoregulation, evaluated by RT-PCR, qPCR and western blotting. Chromatin immunoprecipitation was performed in a cell line, mouse ileum and human IM. Results: CDX2 binds to and transactivates its own promoter and positively regulates its expression in gastrointestinal human carcinoma cell lines. Furthermore, CDX2 is bound to its promoter in the mouse ileum and in human gastric IM, providing a major contribution to understanding the relevance of this autoregulatory pathway in vivo. Conclusion: The results of this study demonstrate another layer of complexity in CDX2 regulation by an effective autoregulatory loop which may have a major impact on the stability of human IM, possibly resulting in the inevitable progression of the gastric carcinogenesis pathway.